Audiovisual Work as a Complex Object of Copyright - L. V. Shvarts (Теоретическая и прикладная юриспруденция)
The article analyzes the construction of an audiovisual work as a complex object from the point of view of coauthorship. To this end, the genesis of the existing subject composition of the authors of an audiovisual work in Russian law is investigated, and approaches to the definition of the authors of an audiovisual work in international legislation are studied. When an audiovisual work is perceived as a multilevel copyright object, its components will be a script, direction, musical accompaniment and other independent works within the framework of the doctrine of a complex copyright object. On the basis of this doctrine, the Russian legislator identifies four authors of an audiovisual work whose creative contribution is the most significant: a production director, a script writer, a composer who created a musical work specifically for an audiovisual work, and a production designer. It is proved that the closed list of authors of an audiovisual work is a characteristic feature of European legal systems that are part of the Romano–Germanic legal family. The Anglo-Saxon approach assumes the granting of all rights to the audiovisual work of the producer.